2020
DOI: 10.1177/1753944720924270
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy in routine management of peripheral arterial disease and intermittent claudication: a scoping review

Abstract: Background: Little is known about the extent to which routine care management of peripheral arterial disease (PAD) and intermittent claudication (IC) align with best practice recommendations on exercise therapy. We conducted a scoping review to examine the published literature on the availability and workings of exercise therapy in the routine management of patients with PAD and IC, and the attitude and practice of health professionals and patients. Methods: A systematic search was conducted in February 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…An additional meta-analysis found that SHE programs were associated with decreased LDL-C, total cholesterol, SBP, and DBP 78 . However, European countries found that the implementation and utilization of SHE programs was still sub-optimal 79 . Given the overwhelming body of evidence to support exercise programs for PAD over the past 30 81 .…”
Section: Regular Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…An additional meta-analysis found that SHE programs were associated with decreased LDL-C, total cholesterol, SBP, and DBP 78 . However, European countries found that the implementation and utilization of SHE programs was still sub-optimal 79 . Given the overwhelming body of evidence to support exercise programs for PAD over the past 30 81 .…”
Section: Regular Physical Activitymentioning
confidence: 99%
“… 78 However, European countries found that the implementation and utilization of structured home-based exercise programs was still suboptimal. 79 Given the overwhelming body of evidence supporting the benefits of exercise programs for PAD over the past 30 years, the American Heart Association (AHA) has endorsed supervised exercise programs (ie, supervised treadmill exercise therapy) for patients with claudication with a Class of Recommendation (COR) I - Level of Evidence (LOE) A recommendation. 80 Alternative strategies for exercise therapy (upper body ergometry, cycling, pain-free/low-intensity walking) are listed as COR IIa - LOE A.…”
Section: Secondary Prevention Involving Patient Participationmentioning
confidence: 99%
“…The disease can cause intermittent claudication, limb ulceration, infections and amputation. Patients usually have limited walking abilities, both regarding duration and speed, with impact to their life quality [1]. This scenario is particularly important due to its relationship with ageing and its well-known cardiovascular risk factor and cardiovascular diseases [18].…”
Section: Peripheral Artery Disease (Pad)mentioning
confidence: 99%
“…However, frequently, the patients overestimate the claudication severity including on the Walking Impairment Questionnaire (WIQ), with many reporting distances falling below the walking treadmill test results. In contrast, distances reported through Information and Communication Technologies (ICT) tools (as Google Maps 1 or Open Street Maps 2 ) have no such discernible trend, suggesting that landmarks-based method is efficient and allows remote control of patient compliance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even when SET is available, patients’ participation is low, mainly because of a lack of transportation and time [ 11 , 12 ]. In addition, reimbursement issues and lack of uptake in health policy plans further hamper the widespread use of SET [ 13 ]. As a result, next to optimal pharmacological treatment, first-line IC management is often limited to a less-effective Go-Home-And-Walk advice.…”
Section: Introductionmentioning
confidence: 99%